PERBEDAAN PENINGKATAN HASIL BELAJAR FISIKA SISWA MENGGUNAKAN MODEL PEMBELAJARAN THINK TALK WRITE DENGAN MODEL PEMBELAJARAN TIME TOKEN - Darmawan Harefa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2020)
This research uses a quantitative approach with a quasi-experimental method. The population this study all VII grade students SMP Negeri 2 Fanayama. The sample this study was class VII-A with a total of 22 students and class VII-B with a total of 24 students. The instrument used was a test of learning outcomes divided into two, namely the initial test and the final test. Based on the results of data processing that has been carried out and the calculation of the hypothesis test obtained tcount = 2.898 ttable = 1.68, then Ho is rejected and Ha accepted it can be concluded that there is a difference in the improvement of student learning outcomes using the Think Talk Write (TTW) learning model with the Time learning model Token then the results the Think Talk Write (TTW) learning model are more favored because this learning model can encourage students to develop and develop the ability to understand the physics material being taught and then write down the core of the material so that students can formulate the knowledge acquired in the language itself compared to the Time Token learning model